2021
DOI: 10.1002/art.41531
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RELA Truncating Mutation in a Familial Behçet’s Disease–like Mucocutaneous Ulcerative Condition

Abstract: Objective. Monogenic Behçet's disease (BD)-like conditions are increasingly recognized and to date have been found to predominantly involve loss-of-function variants in TNFAIP3. This study was undertaken to identify genetic and pathobiologic mechanisms associated with a BD-like mucocutaneous ulcerative syndrome and neuromyelitis optica (NMO) occurring in 3 generations of an Irish family (n = 5 cases and 5 familial controls). Methods. Whole-exome sequencing was used to identify potential pathogenic variants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…RelA is also known as p65 and is critically involved in nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) heterodimer formation and consequent activation of NF-κB-mediated proinflammatory signalling. RelA haploinsufficiency has been reported as a cause of chronic mucocutaneous ulceration and familial Behçet’s disease (46, 47). Badran et al reported a family of four affected family members with mucocutaneous ulceration harbouring a mutation in the canonical donor splice site of exon 6 (NM_021975:c.559+1G>A), likely leading to a premature stop codon and haploinsufficiency (46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RelA is also known as p65 and is critically involved in nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) heterodimer formation and consequent activation of NF-κB-mediated proinflammatory signalling. RelA haploinsufficiency has been reported as a cause of chronic mucocutaneous ulceration and familial Behçet’s disease (46, 47). Badran et al reported a family of four affected family members with mucocutaneous ulceration harbouring a mutation in the canonical donor splice site of exon 6 (NM_021975:c.559+1G>A), likely leading to a premature stop codon and haploinsufficiency (46).…”
Section: Resultsmentioning
confidence: 99%
“…Although RELA has already been reported as an IEI gene in a previous IUIS classification (48), it was not yet listed in the IEI in silico gene panel of our Department of Human Genetics (25), because evidence was considered insufficient at the time. Based on these arguments, this DNV has only now been classified as pathogenic, which could carry implications for therapy with anti-tumour necrosis factor alpha (TNFα) inhibitors (47).…”
Section: Resultsmentioning
confidence: 99%
“…Haploinsufficiency for RELA has been reported to present with mouth and genital ulcers, recurrent fever, colitis and mucocutaneous ulceration ( 105 , 106 ). Ulceration was attributed to heightened sensitivity to the apoptotic effects of TNF.…”
Section: Inborn Errors Of Nf-κb and Skin Pathologymentioning
confidence: 99%
“…Using WES, Adeeb et al recently identified five familial cases of a novel RELA -truncating mutation that resulted in BD-like mucocutaneous ulcerations and neuromyelitis optica in three generations of an Irish family [ 108 ]. Data from this case series indicated that loss-of-function mutations in RELA impaired NF-κB signalling and increased apoptosis, causing the BD-like phenotype [ 108 ] ( Figure 1 C).…”
Section: Mimics Of Bdmentioning
confidence: 99%